After High School - What? - Berdie, Ralph F. (Ralph Freimuth), 1916- (Book collections on Project MUSE., 1954)
After High School - What? was first published in 1954. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. Whether a high school graduate enters college, goes to work, takes vocational training, or follows any other path open to him is of concern not only to the youth himself but to the nation and its manpower needs. This study throws light on the question of what influences determine the decision for a college education. It is based on information obtained from 25,000 graduating high school seniors in Minnesota, interviews with a sampling of their parents, and a follow-up study to check on how closely the young people followed the plans they indicated in the original survey. The book, a volume in the Minnesota Library on Student Personnel Work, will be helpful to high school and college administrators and counselors.